PENGARUH SANCTIFICATION TERHADAP KEPUASAN PERNIKAHAN: PERAN MEDIASI OLEH POSITIVE DYADIC COPING - Sindoro, Lidwina Florentiana; Sari, Yudiana Ratna (Jurnal Psikologi : Media Ilmiah Psikologi, 2022)
The research about protective factors in marital satisfaction guides the researchers to observe spouse spirituality factors in marriage. The research aims to understand the mediation positive dyadic coping effect that bridges positive sanctification of marriage effect and marital satisfaction. Mediation analysis with SPSS macro PROCESS results direct effect sanctification of marriage on marital satisfaction (F(1, 122) = 11.091, p < 0.05)). Sanctification of marriage has proven positive and significant to predict marital satisfaction as a dependent variable (c = 1.307, p < 0.000). The more the person understands marriage as the revelation of God, the marital satisfaction increases. Indirect effect demonstrates a significant result (a*b = 0.76, 95% CI [0.18, 1.41]) with effect size as 0.168. Therefore, positive dyadic coping is a significant mediator between sanctification of marriage and marital satisfaction. The more the person has a notion that marriage is God’s revelation, that person uses the positive dyadic coping more often, the marital satisfaction of that person increases